2008
DOI: 10.1111/j.1540-8167.2008.01111.x
|View full text |Cite
|
Sign up to set email alerts
|

Time‐Dependence of Appropriate Implantable Defibrillator Therapy in Patients with Ischemic Cardiomyopathy

Abstract: In a routine clinical practice primary prevention population with prior MI and LVEF

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0
9

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 17 publications
4
29
0
9
Order By: Relevance
“…7 Also, previous primary prevention observational studies showed similar incidences of appropriate therapy after 5-7 years of follow-up. [11][12][13]20 Appropriate shocks were observed in 24% of the primary prevention patients and 47% of the secondary prevention patients over 12 years, which seems comparable with the 28% appropriate shocks reported by Ronn et al after 6 years in secondary prevention patients. 10 Furthermore, the large ALTITUDE registry reported 33%-38% appropriate shocks after 5 years.…”
Section: Appropriate Device Therapysupporting
confidence: 90%
“…7 Also, previous primary prevention observational studies showed similar incidences of appropriate therapy after 5-7 years of follow-up. [11][12][13]20 Appropriate shocks were observed in 24% of the primary prevention patients and 47% of the secondary prevention patients over 12 years, which seems comparable with the 28% appropriate shocks reported by Ronn et al after 6 years in secondary prevention patients. 10 Furthermore, the large ALTITUDE registry reported 33%-38% appropriate shocks after 5 years.…”
Section: Appropriate Device Therapysupporting
confidence: 90%
“…W przypadku wyczerpania baterii urządzenia lub konieczności jego usunięcia nie należy automatycznie zastę-pować go nowym [234][235][236][237][238]. Przed ponowną implantacją pacjent powinien być poddany konsultacji przez doświadczo-nego kardiologa, ponieważ cele leczenia mogły się zmienić, ryzyko wystąpienia groźnych arytmii może być mniejsze, a ryzyko zgonu z innych powodów istotnie wyższe.…”
Section: Prewencja Pierwotna Nagłego Zgonu Sercowegounclassified
“…Przed ponowną implantacją pacjent powinien być poddany konsultacji przez doświadczo-nego kardiologa, ponieważ cele leczenia mogły się zmienić, ryzyko wystąpienia groźnych arytmii może być mniejsze, a ryzyko zgonu z innych powodów istotnie wyższe. Przedmiotem dyskusji wciąż pozostaje pytanie, czy u pacjenta, u którego doszło do istotnej poprawy LVEF, i u którego nie stwierdzano interwencji urządzenia przed wyczerpaniem baterii, powinno się ponownie wszczepić ICD [234][235][236][237][238].…”
Section: Prewencja Pierwotna Nagłego Zgonu Sercowegounclassified
“…In addition, the ICD lead has been implicated in eliciting an arrhythmia by local mechanical perturbation just as a catheter may trigger ectopy when present in the ventricle (or atrium) during a catheterisation 81. Local, lead-related proarrhythmia may partly explain a higher incidence of a first VT/VF event in the first year after a prophylactic ICD implant than in the second or later years as was observed in some ICD trials11 and one single centre experience 82. Although cardiac resynchronisation therapy (CRT) devices can reduce VT/VF occurrence in LBBB patients83 the effect is not always noted,84 and there are numerous anecdotal cases of proarrhythmia attributed to biventricular pacing 85 86…”
Section: Acute Complicationsmentioning
confidence: 99%